Outcomes and biomarker analyses among patients with COVID-19 treated with interleukin 6 (IL-6) receptor antagonist sarilumab at a single institution in Italy - Vincenzo Montesarchio; Paolo Antonio Ascierto; Antonio Maria Grimaldi; Marcello Curvietto; Domenico Mallardo; Marco Palla; Chiara Iommelli; Antonella Bianco; Elio Manzillo; Fiorentino Fraganza; Cristiana Palumbo; Gaetano Rea; et al. (Journal for ImmunoTherapy of Cancer)
Background The inflammatory pathology observed in severe COVID-19 disease caused by the 2019 novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by elevated serum levels of C reactive protein (CRP) and cytokines, including interferon gamma, interleukin 8 (IL-8), and interleukin 6 (IL-6). Initial reports from the outbreak in Italy, China and the USA have provided anecdotal evidence of improved outcomes with the administration of anti-IL-6 agents, and large-scale trials evaluating these therapies are ongoing.Study description In this retrospective case series, clinical outcomes and correlates of response to treatment with the IL-6 receptor antagonist sarilumab are described for 15 patients with COVID-19 from a single institution in Southern Italy. Among 10 patients whose symptoms improved after sarilumab treatment, rapid decreases in CRP levels corresponded with clinical improvement. Lower levels of IL-6 at baseline as well as lower neutrophil to lymphocyte ratio as compared with patients whose COVID-19 did not improve with treatment were associated with sarilumab-responsive disease.Conclusions This observation may reflect a possible clinical benefit regarding early intervention with IL-6-modulatory therapies for COVID-19 and that CRP could be a potential biomarker of response to treatment.